(untitled) (Research, Society and Development, 2022)
Silver nanoparticles (AgNP) obtained from biological synthesis can be widely used in industrial and medical fields because of their observed antimicrobial activity. The objective of this study was to analyze the biosynthesis of AgNPs by the fungus Lentinus crinitus (L.) Fr., and to evaluate the potential of these nanoparticles as antimicrobial agents. The antimicrobial activity of AgNPs was evaluated by agar diffusion, and broth microdilution methods to determine the minimum inhibitory concentration (CMI) against Staphylococcus aureus, Escherichia coli, Candida albicans and Candida tropicalis. AgNPs were characterized by UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), inductively coupled plasma emission spectrometry (ICP) and transmission electron microscopy (TEM). The UV-Vis spectra of the reaction mixture showed a SPR band with peak absorbance at 423 nm, confirming the presence of AgNPs. The synthesized AgNPs demonstrated antagonistic action against C. tropicalis (1.88 µg. mL-1), C. albicans (30.09 µg. mL-1), E. coli and S. aureus (7.52 µg. mL- 1). The AgNPs mediated by L. crinitus are mostly spherical, triangular and rod-shaped (mean diameter 8.82 nm). The concentration of silver in their crystalline structure is 120.37 µg / mL, and protein residues as possible stabilizers. The Lentinus crinitus mushroom isolated from substrates of the Amazon biome is a promising bio-resource for the biological synthesis of AgNPs with relevant antimicrobial properties and demonstrating a great potential for its application in pharmaceutical and food industries.